Energizing Education: Fostering Interactive Engagement in Basic Electronics through STEM-Project Based Learning - Nehru Nehru; Sri Purwaningsih; Cicyn Riantoni; Devie Novallyan (AL-ISHLAH: Jurnal Pendidikan, 2024)
The learning setting refers to the combined social, psychological, and pedagogical circumstances which have the potential to impact students' learning, accomplishments, and attitudes. This research aims to analyze the STEM-Project Based Learning environment in the Basic Electronics course. The research method used is quantitative with a survey design. The research subjects are 65 students enrolled in the Basic Electronics course in the Physics Education program at the University of Jambi. Data collection is conducted through surveys. The survey instrument uses the WIHIC instrument. The research findings indicate that out of the 7 WIHIC indicators, namely student cohesiveness, teacher support, involvement, order and organization, task orientation, cooperation, and equity, data reveals that there are still issues in the implementation of STEM-Project Based Learning, particularly in the areas of teacher support and involvement. As an illustration, data indicates that 42.9% of students perceive that the teacher occasionally succeeds in engaging their attention during STEM-Project Based Learning. On the other hand, positive aspects are frequently observed in the equity indicator. This is evident in STEM-Project Based Learning, where 50% of the students feel they are given equal opportunities to answer questions during discussions.